2021
DOI: 10.3390/rs13163078
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Gas Flaring in Russia with Multispectral VIIRS Nightfire

Abstract: According to the data reported by the international and governmental agencies, the Russian Federation remains one of the world’s major associated petroleum gas (APG) flaring nations. In the past decade, numerous studies have shown the applicability of satellite-based methods to estimate gas flaring. New satellite-based observations might offer an insight in region-, company-, and site-specific gas flaring patterns, as the reported data are often incomplete. We provide a detailed catalog of the upstream and dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Economic benefits, commonly prioritised by oil and gas-rich nations over climate change concerns, are the main barriers to functional policy implementation (Korppoo, 2018b;Ylä-Anttila et al, 2018). Various studies (including those by Svensson, 2005;Castelo Branco, Szklo and Schaeffer, 2010;Loe and Ladehaug, 2012;Buzcu-Guven and Harriss, 2014;Olusegun G Fawole, Cai and Mackenzie, 2016;Korppoo, 2018c;Mrabure and Ohimor, 2020;Olujobi and Olusola-Olujobi, 2020;Zhizhin et al, 2021;Rodrigues, 2022;Bello, 2023;Shahab-Deljoo et al, 2023;Wen, Xiao and Peng, 2023) have identified the need for an enabling framework including fiscal incentives and emission reduction incentives for investments and a weak natural gas market and tax reductions to reduce flaring. However, the extent to which this criterion hinders flaring reduction globally has not been sufficiently researched.…”
Section: Discussionmentioning
confidence: 99%
“…Economic benefits, commonly prioritised by oil and gas-rich nations over climate change concerns, are the main barriers to functional policy implementation (Korppoo, 2018b;Ylä-Anttila et al, 2018). Various studies (including those by Svensson, 2005;Castelo Branco, Szklo and Schaeffer, 2010;Loe and Ladehaug, 2012;Buzcu-Guven and Harriss, 2014;Olusegun G Fawole, Cai and Mackenzie, 2016;Korppoo, 2018c;Mrabure and Ohimor, 2020;Olujobi and Olusola-Olujobi, 2020;Zhizhin et al, 2021;Rodrigues, 2022;Bello, 2023;Shahab-Deljoo et al, 2023;Wen, Xiao and Peng, 2023) have identified the need for an enabling framework including fiscal incentives and emission reduction incentives for investments and a weak natural gas market and tax reductions to reduce flaring. However, the extent to which this criterion hinders flaring reduction globally has not been sufficiently researched.…”
Section: Discussionmentioning
confidence: 99%
“…The VIIRS Nightfire data set (Elvidge et al, 2013;Elvidge et al, 2015;EOG, 2023;Zhizhin et al, 2021) was processed for annual natural gas flared volume in the U.S. from 2017 to 2020 (Figure 1). In 2019, the year with highest flare gas volume during the above period, there were 17.7 BCM of natural gas flared in both production (97%) and processing (3%)-the same amount of flare gas volume was reported in Chen et al (2022).…”
Section: Flare Emissions Estimation From Viirsmentioning
confidence: 99%
“…The method of flooding with aqueous solutions of surfactants can be effectively used in strictly defined geological and physical conditions, as evidenced by many years of experience (since 1971) in the use of surfactants in Tataria to enhance oil recovery from terrigenous Devonian deposits, as well as the use of surfactants in the Samotlor field [31,32]. Numerous experimental studies carried out at «TatNIPIneft» have shown that the use of concentrated surfactant solutions under conditions of primary oil displacement from models of terrigenous rocks significantly improves the process of oil displacement.…”
Section: Surfactant Compositionsmentioning
confidence: 99%